1989
DOI: 10.1093/ageing/18.5.333
|View full text |Cite
|
Sign up to set email alerts
|

Calcification on Chest Radiographs: The Association with Age

Abstract: Seven hundred chest radiographs taken in a general hospital were reviewed, 100 (50 men and 50 women) from each of seven decades (3rd to 9th). Each radiograph was examined to determine the site and extent of calcific changes. Prevalence of costal cartilage calcification increased from 6% in the 3rd decade to 45% in the 9th and was commoner in men. Aortic calcification was absent below age 50 and increased from 4% in the 6th decade to 57% in the 9th. Both these trends were statistically significant. Other sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Exertional dyspnea in elderly people can occur due to this cause. Apart from the age group of 41-50 years, males are affected more than females in all age groups which is consistent with findings of Charles Teale (1989) [6]. King JB (1939) observed that calcification of costal cartilages is rare before age of twenty and occur with advancing age which is observed more frequently and more extensively in costal cartilage of first rib than others and established that the condition begins at an earlier age in the male sex.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Exertional dyspnea in elderly people can occur due to this cause. Apart from the age group of 41-50 years, males are affected more than females in all age groups which is consistent with findings of Charles Teale (1989) [6]. King JB (1939) observed that calcification of costal cartilages is rare before age of twenty and occur with advancing age which is observed more frequently and more extensively in costal cartilage of first rib than others and established that the condition begins at an earlier age in the male sex.…”
Section: Discussionsupporting
confidence: 87%
“…He examined each radiograph to determine the site and extent of calcific changes in costal cartilages. He observed that prevalence of costal cartilage calcification increased from 6% in the 3 rd decade to 45% in the 9 th decade and was commoner in men [6]. Barchilor V (1996) studied the extent of costochondral ossification of the first rib from 78 chest radiographs of 13 healthy male soldiers subjected to a periodic follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent cartilages almost never calcify and ossify, or if they do their ossification is incomplete and occurs at the end of adolescence or under pathological conditions [1][2][3][4]. The costal cartilages are invisible on radiograph images unless they are calcified or ossified.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of calcificated costal cartilages has been investigated by many authors in the last century. Authors have attempted to correlate costal cartilage calcification with arteriosclerosis, infections (especially tuberculosis), mineral metabolism and nutrition [1,2,[5][6][7] genetical, physical and kinetic breathing factors and also ethnical factors were studied [8][9][10][11]. The results of these studies are uncertain and unconvincing, with the exception of linking ossification with genetic influences.…”
Section: Introductionmentioning
confidence: 99%